Process-oriented dynamic capabilities: Framework development, empirical applications, and methodological support: Print zugl.: Münster (Westfalen), Univ., Diss., 2013 - Plattfaut, Ralf (Springer International Publishing, 2014)
This book introduces a process-oriented dynamic capability framework to study both, service innovation and Business Process Management (BPM). Results from applications in several case studies and surveys are reported. They reflect, e.g., capability development and maturity models. Based on these findings, a method to support service innovation is introduced. This method can help organizations in developing new service business models in a more effective and efficient way. In today’s networked service society, service innovation becomes increasingly important. Reasons for this development can be found in the transformation of economies and in the growing importance of product-service systems. The concept of service innovation is related to Business Process Management (BPM) and shares several important traits. They both are process-oriented dynamic capabilities to adapt (service) processes to changing environments